The effect of molasses, tapioca and sago flour on biofloc system and volume of growth performance in whiteleg shrimp Litopenaeus vannamei - Tamrin Tamrin; Muhammad Aris; Waisya Ade Muntahar; Taufiq Abdullah (Depik, 2025)
Despite the high commercial success the whiteleg shrimp industry has achieved, challenges related to water quality and disease remain major issues. One approach to address these problems is Biofloc Technology (BFT). Carbon sources have been one of the factors influencing the characteristics of BFT. Some organic carbon sources used include molasses, tapioca flour, and sago flour. This study aimed to evaluate and compare the use of molasses, tapioca flour, and sago flour as organic carbon sources in BFT. It focused on examining, their impact on floc density and the growth performance of whiteleg shrimp. The study was conducted from November to December 2023 using a completely randomized design with treatments including a control, molasses, tapioca flour, and sago flour, each with three replicates. Parameters measured included biofloc volume, weight gain, average daily growth, survival rate, and feed conversion ratio. The results showed that BFV treatments with molasses, tapioca flour, and sago flour had significant differences compared to the control group. Sago flour provided a significant increase in BFV. The growth performance of whiteleg shrimp in treatments with molasses, tapioca flour, and sago flour improved and showed significant differences compared to the control. The application of BFT using molasses, tapioca flour, and sago flour as organic carbon sources significantly enhanced the biofloc volume, growth performance, feed conversion ratio, and survival rate of whiteleg shrimp. Among the tested carbon sources, sago flour demonstrated the highest biofloc volume and the most significant improvement in shrimp growth and feed efficiency.Keywords:Biofloc technologyMolassesSago flourTapioca flourWhiteleg shrimp